Development of reverse dot blot hybridisation strip assays to identify common beta-thalassaemia alleles in Malays and Chinese in Malaysia - Teh, Lai Kuan (2010)
Beta-thalassemia is the most common autosomal genetic disorder in Malaysia particularly among Malays and Chinese-Malaysians. The heterozygous carrier frequency of β-thalassaemia in Malaysia is estimated to be 4.5% from micro-mapping studies. The spectrum of β-thalassaemia mutations differs in each ethnic group in Malaysia. There are four to five common mutations responsible for more than 95% of the mutations seen in each ethnic group respectively. The current diagnostic method in Malaysia, amplification refractory mutation system (ARMS-PCR), is only able to identify one mutation in each reaction. It is found labour intensive and time consuming when few mutations need to be identified. Therefore, there is a need to have an effective and accurate laboratory method that can identify common mutations simultaneously in each ethnic group.In this study, the reverse dot blot hybridization (RDBH) technique was used in development of strip assays for characterisation of the β-thalassaemia mutations. Two strip assays were designed specifically for Malays and Chinese-Malaysians respectively with each strip to identify six common mutations simultaneously. The mutations identified with the strip assays were validated with the gold standard method, ARMS-PCR. A total of 177 patients (354 alleles) from University Malaya Medical Centre (UMMC) and the Institute of Medical Research (IMR) in Malaysia were studied. One hundred and thirty seven were Malays (274 alleles) and 40 were Chinese-Malaysians (80 alleles) respectively. One hundred and nineteen (86.9%) Malay patients consisting of 238 alleles were identified by the RDBH-Strip M(6). In the Malays, the most common β-thalassaemia mutations identified was CD 26, followed by IVS I-5, IVS I-1, CD 19 and the least with CD 8/9. In view of possible inter-marriage with Chinese, the RDBH-Strip C(6) was used to identify the 18 unidentified alleles in the Malays. The mutations identified were common Chinese mutations, CD 41/42 (5 heterozygous), CD 17 (2 heterozygous), -29 (2 heterozygous) and CD 71/72 (1 homozygous). Thus, a total of 129 (94.6%) Malay patients consisting of 258 alleles were identified using the RDBH-Strip Assays [RDBH-Strip M(6) and RDBH-Strip C(6)] . In the Chinese-Malaysians by the RDBH-Strip C(6), mutations were identified in 32 (80%) patients consisting of 64 alleles. IVS II-654 and CD 41/42 were the two most common β-thalassaemia mutations amongst Chinese-Malaysians, followed by CD17 and -28. In the Chinese-Malaysians, RDBH-Strip M(6) identified CD 26 (3 heterozygous) and IVS I-5(1 heterozygous). Thus, a total of 36 (90.0%) Chinese-Malaysians patients consisting of 72 alleles were identified using the RDBH-Strip Assays [RDBH-Strip C(6) and RDBH-Strip M(6)] . The RDBH-Strip Assays developed in this project study identified 93.2% of the mutations seen in the Malays and Chinese-Malaysians. There were remaining 11 heterozygous beta-thalassaemia carriers (eight Malays and four Chinese) whose mutations could not be identified. These unknown mutations require DNA sequencing for ultimate diagnosis. ARMS-PCR was used to confirm and validate the presence of the six mutations used in the RDBH-Strip Assays. It amplified each mutation as a separate and distinct PCR product. The Strip Assays showed 100% sensitivity and specificity through validation by ARMS-PCR. Therefore, the Strip Assay can be defined as a reliable diagnostic tool for accurate beta-thalassaemia mutation identification in Malays and Chinese Malaysians. In conclusion, the developed RDBH- Strip Assays [M(6) and C(6)] are accurate and rapid diagnostic tools for the identification of beta-thalassaemia mutations in the Malays and Chinese-Malaysians.